Powder Interlayer Bonding of Nickel-Based Superalloys with Dissimilar Chemistries - Olivia Stanners Stanners (Materials, 2021)
Novel joining methods are crucial for the aerospace industry to repair components damaged in the high stress, high cycle environment of the jet turbine engine. Powder interlayer bonding (PIB) is a novel joining technique that is being explored for use in the aerospace industry. PIB involves the use of a powder interlayer between two faying surfaces alongside a localised temperature gradient and compressive force to produce one joined workpiece. The use of a localised temperature gradient not only reduces the heat affected zone (HAZ) but also reduces the energy requirements for the process as only a small area of the component needs to be elevated in temperature. Nickel-based superalloys are commonly used in the gas turbine engine due to their superior mechanical properties that are maintained even under the most elevated temperatures experienced in the jet turbine engine. It is therefore essential these alloys can be easily repaired. Conventional joining methods such as friction welding have proved difficult for new generation nickel-based superalloys; therefore, there is much interest in PIB as an alternative repair technology. This study shows the potential of PIB to join dissimilar nickel-based superalloys: bonds with very little porosity were observed after only a short processing time.